Expression of a Surface Antigen (MA6) by Peripheral Blood CD34(+) Cells Is Correlated with Improved Platelet Engraftment and May Explain Delayed Platelet Engraftment Following Cord Blood Transplantation - Simmons, Paul J. (Stem Cells Dev, 2015)
CD34(+) cell dose provides a measure of hematopoietic tissue that predicts the rate of engraftment upon transplant. It is positively correlated with multiple measures of hematopoietic recovery, including platelet engraftment. Here we identify a subpopulation of CD34(+) cells that coexpress a surface antigen—MA6, which is more positively correlated with platelet engraftment in a clinical setting than CD34(+) alone. The specific identity and function of MA6 remain to be determined, however, it is expressed by primitive megakaryocyte (MK) progenitors, but is lost with differentiation and is not expressed by platelets. Commitment of CD34(+)MA6(+) cells to the MK lineage was confirmed by in vitro assays and their significance in hematopoietic transplantation explored by flow cytometric analysis of cryopreserved samples of granulocyte colony stimulating factor-mobilized peripheral blood progenitor cell (PBPC) products along with a retrospective analysis of platelet engraftment data. Platelet engraftment by day 21 was predicted by receipt of ≥6×10(6) CD34(+) cells/kg or ≥0.3×10(6) CD34(+)MA6(+) cells/kg. Subsequent analysis of cord blood (CB) CD34(+) cells revealed <0.2% coexpressed MA6(+), compared to 8% of PBPC CD34(+) cells. This low proportion of CD34(+)MA6(+) cells may be responsible, at least in part, for the delayed platelet engraftment associated with CB transplantation. However, platelet engraftment is markedly improved in recipients of ex vivo-expanded CB. This may be a consequence of an increased proportion of CD34(+)MA6(+) cells present in the ex vivo-expanded product and also suggests that optimizing ex vivo culture conditions to generate CD34(+)MA6(+) cells might further improve platelet engraftment in CB recipients.